Tourist Safety Risk Management at Tourist Attraction in Upang River - Pusparini, Marissa; Lestari, Zakia Ayu (International Journal of Magistravitae Management, 2024)
This study aims to investigate tourism development strategies in the Sungai Upang Conservation Area, located in Bangka Belitung Province, Indonesia. Sungai Upang is a tourist destination renowned for its rich biodiversity and natural landscapes, officially designated as a conservation area in 2017. The management of the Sungai Upang Conservation Area actively involves local community participation through organizations such as the Bangka Flora Society (a local environmental organization), Sahabat Alam Sungai Upang (Friends of Nature Sungai Upang), and Pokdarwis (Kelompok Sadar Wisata or Tourism Awareness Group), which promote sustainable tourism and environmental preservation. This study employed a qualitative research approach, utilizing in-depth interviews with key management personnel and direct site observations. The findings indicate that tourism development strategies in Sungai Upang focus primarily on promoting eco-tourism and conservation education. The local government and the State Electricity Company (Perusahaan Listrik Negara or PLN) have supported infrastructure and facility development in the area to increase tourist visits and enhance the economic welfare of the local community. However, the rising number of visitors has introduced potential risks and challenges that must be addressed. This study identified several risks, including environmental degradation, safety concerns, and management inefficiencies. To mitigate these risks, the study recommends implementing a comprehensive risk management system that includes the development of safety protocols, continuous environmental monitoring, and stronger community engagement in the management process. The findings of this study offer valuable insights for the sustainable development of tourism in the Sungai Upang Conservation Area and can serve as a reference for similar ecotourism contexts. Additionally, this study contributes to a deeper understanding of the complex relationship between tourism development, environmental conservation, and risk management in ecologically sensitive destinations.